Identification and Detection of CYP4G68 Overexpression Associated With Cyantraniliprole Resistance in Bemisia tabaci From China - Wang, Ran; Che, Wunan; Qu, Cheng; Wang, Jinda; Luo, Chen (Frontiers in Environmental Science, 2022)
Bemisia tabaci, the tobacco whitefly, is one of the most notorious agricultural sucking insect pests that severely damages a series of crops worldwide. Throughout China, B. tabaci threatens agricultural production with increasing cases of resistance to commonly used insecticides, prompting the widespread use of cyantraniliprole as an alternative to control hemipteran pests. Here, we found overexpression of the CYP4G68 gene conferring cyantraniliprole resistance by quantitative real-time PCR (qPCR) and RNA interference (RNAi) in one lab-selected resistant strain CYAN-R (to about 80-fold higher than control). Furthermore, we measured levels of resistance to cyantraniliprole in whitefly with 18 field-sampled populations across China, and then confirmed that, among them, 14 field-sampled populations showed from low to high resistance to cyantraniliprole compared with the susceptible strain. We measured CYP4G68 expression in the 14 field populations, and results of qPCR and RNAi indicated that in two of these populations, Haikou and Wuhan, significant overexpression of CYP4G68 contributed to development of field-evolved resistance to cyantraniliprole. These results facilitate strategies of management to delay the evolution of resistance to cyantraniliprole and control of whiteflies more sustainably, and to prevent overuse of insecticides in the environment through rational application practices.